Motivasi Belajar Lanjutan Lulusan Program Kelompok Belajar Paket A - Ishak Abdulhak (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study aimed to investigate the correlation between learners’ achievement and their motivation to attend further level of education and to get better income after graduating from Package A Study Group Program. A number of 299 graduates of Package A1-A20 Program in Bandung were involved. The results indicate that there was a significant correlation between learners’ achievement and their motivation to attend higher level of education and to get better income. It means that when learners achieved better, their motivation to continue their study and to earn better was increasing. In other words, Package A program can be used as an income generating